Influence of milk production records on the estimation of typical and extended curve lactation parameters in local goats under grazing management - TORRES-HERNÁNDEZ, GLAFIRO; MALDONADO-JÁQUEZ, JORGE A.; SALINAS-GONZÁLEZ, HOMERO; GRANADOS-RIVERA, LORENZO DANILO; J. PASTOR-LÓPEZ, FRANCISCO; VAQUERA-HUERTA, HUMBERTO; BAUTISTA-MARTÍNEZ, YURIDIA (The Indian Journal of Animal Sciences, 2020)
The effect of measure number of milk production (MP) on the estimation of parameters in typical and extended lactations curve parameters of local goats was evaluated. This study was conducted with 14 producers in 5 communities of the Comarca Lagunera, State of Coahuila, México. MP was measured monthly by hand-milking during 4 years. Data analyzed included 12,097 observations belonging to 2,229 lactations from 1,125 local goats. The Wood model was utilized to characterize the lactation curve and its parameters (a, b, and c). Two groups were formed, G1 (typical lactation with 3-7 milk measures), and G2 (extended lactations with 8-10 milk measures). The criterion utilized to determine the adequate number of MP measures during lactation was the standard error of the estimate. The best fit in the estimation of the curve parameters was obtained in G2. Factors affecting the curve parameters were also evaluated utilizing the MIXED procedure of SAS. Community, year, and parity number influenced all the parameters in both groups. Flock within community influenced b and c in G1. Season of parity influenced c in G2. It is concluded that a higher measure number of MP in an extended lactation helps in better estimation of lactation curve parameters.